1991
DOI: 10.1007/bf01627989
|View full text |Cite
|
Sign up to set email alerts
|

The normal uterus on magnetic resonance imaging and variations associated with the hormonal state

Abstract: Magnetic Resonance Imaging of the pelvis has lead to a new radioanatomical description of the uterus. Variations in the anatomical zones of the uterus were noted with different sequences used in MRI. There was also structural and signal variation depending on hormonal impregnation. Twenty seven MRIs of pelvices were carried out on 16 female volunteers. Eight of them were on oestroprogesterone as the method of contraception (Group I) and had a single MRI. Six were not taking contraceptives (Group II) and had di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 9 publications
5
19
0
2
Order By: Relevance
“…This finding is consistent with previous studies demonstrating decreasing cervical and uterine corpus lengths as women progress past the menopausal transition [6, 20]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous studies demonstrating decreasing cervical and uterine corpus lengths as women progress past the menopausal transition [6, 20]. …”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have identified various demographic factors associated with the size of the uterine corpus and cervix, including age/menopausal status and parity [6, 2022]. Based on the data from these papers, we would predict, for example, that multiparous, premenopausal women are more likely to have larger uteri and cervices.…”
Section: Discussionmentioning
confidence: 99%
“…( Z5), in an unpaired study of nine women taking oral contraceptives (oestrogenprogestin combinations) for a mean of 7 years, were able to detect changes of 65-78% in endometrial width (corresponding probably to >90% in volume). Similar values were reported in a study by Bartoli et al ( 18). Table 4 suggests that changes as much as an order of magnitude smaller could be detectable.…”
Section: Discussionsupporting
confidence: 86%
“…10 In support of this association between cervical length and prolapse, Berger et al correlated both cervical length and difference between the measurements of point C and D with POPQ stage and found that women with prolapse (as defined as at least anterior wall reaching 1 cm outside of hymen) had longer cervix greater distance between point C and D. 10 However, this study had one major limitation: the cervical length was the total length measured on MRI, from the external to the internal os, which does not reflect the relationship between length of the vaginal portio, which arguably is the relevant one when support is assessed on physical examination during POPQ measurements. One can see that to reach Point C from Point D, one not only has to come down the length of the exocervix from D to the edge of the posterior cervix, but then across the cervical width to the edge of the anterior cervix, where is located One prior small study investigated the influence of hormonal state on cervical size, 11 which was congruent with ours. Bartoli et al used MRI to assess the uterus of 16 volunteers: eight nulligravida on cyclical contraception, six women naturally cycling (one of them parous), and two nulliparous postmenopausal women (one on estrogen replacement).…”
Section: Discussionsupporting
confidence: 85%